2022
DOI: 10.1101/2022.12.06.519316
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Itch receptor MRGPRX4 interacts with the receptor activity-modifying proteins (RAMPs)

Abstract: Cholestatic itch is a severe and debilitating symptom in liver diseases with limited treatment options. The class A G protein-coupled receptor (GPCR) Mas-related GPCR subtype X4 (MRGPRX4) has been identified as a receptor for bile acids, which are potential cholestatic pruritogens. An increasing number of GPCRs have been shown to interact with receptor activity-modifying proteins (RAMPs), which can modulate different aspects of GPCR biology. Using a combination of multiplexed immunoassay and proximity ligation… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…Nonetheless, the observed behavioral phenotype may be exaggerated or skewed by the nonphysiologic amounts of receptor expression. A recent study identified the presence of human receptor activity–modifying proteins (RAMPs) that modulate MRGPRX4 expression ( 43 ). It is unclear whether MRGPRX4 can also be regulated by the murine RAMP counterpart.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, the observed behavioral phenotype may be exaggerated or skewed by the nonphysiologic amounts of receptor expression. A recent study identified the presence of human receptor activity–modifying proteins (RAMPs) that modulate MRGPRX4 expression ( 43 ). It is unclear whether MRGPRX4 can also be regulated by the murine RAMP counterpart.…”
Section: Discussionmentioning
confidence: 99%
“…Given our demonstrated structural differences between S83 and the previously published L83, even individual amino acid changes in this highly variable sequence can have profound impacts on receptor activation. Furthermore, RAMP2 was reported to down-regulate the surface expression of MRGPRX4 ( 43 ). This finding highlights a regulatory mechanism that could also shape the representation of itch.…”
Section: Discussionmentioning
confidence: 99%
“…The plasmids encode an N-terminal 3xHA tag (amino acid sequence YPYDVPDYA) following the signal peptide (SP; amino acids 1 to 26, 1 to 42, and 1 to 27 for RAMP1, RAMP2, and RAMP3, respectively) and two C-terminal OLLAS tags (amino acid sequence SGFANELGPRLMGK) linked by a flexible spacer that also includes two Strep-tag II peptides (amino acid sequence WSHPQFEKGGGSGGGSGGGSWSHPQFEK). Each 3xHA-RAMP-OLLAS construct was generated using the TagMaster site-directed mutagenesis kit according to the manufacturer’s instructions for “long-range mutation” as previously reported ( 36 ) using the previously validated FLAG-RAMP-OLLAS construct as a starting point ( 9 ). All constructs were confirmed by sequencing in the forward and reverse directions (T7, BGHR primers) (Genewiz).…”
Section: Methodsmentioning
confidence: 99%